Immunoglobulin-mediated immune dysregulation in recurrent pregnancy loss: mechanisms, biomarkers, and therapeutic perspectives - Kamala C; Pallavi Shekar; Umme Kulsum; Ananya Hegde; Lakshitha V Jayakrishna; Deepa Bhat; Meghana Hangala Shivakumaraswamy; Akila Prashant; Praveen Kumar K S (Immunologic Research, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disease that is typified by repeated pregnancy loss with immune dysregulation emerging as a critical contributing factor. Immunoglobulins are among the immune components that are instrumental in preserving tolerance between the mother and the fetus, regulating inflammatory responses, and supporting placental development. This review provides a comprehensive overview of the role of immunoglobulins in recurrent pregnancy loss, with particular emphasis on immune dysregulation, emerging biomarkers, and therapeutic implications. The immunoglobulin profiles, such as the changes in IgG subclasses and the presence of pathogenic autoantibodies, e.g. antiphospholipid and antinuclear antibodies, are highly correlated with unfavourable pregnancy outcomes. These changes, in a mechanistic manner, lead to poor trophoblast invasion, endothelial dysfunction, thrombosis and cytokine imbalance. Emerging evidence also highlights the contribution of regulatory B cells and the antibody-mediated immune network in maintaining pregnancy homeostasis. Immunoglobulin profiling has clinical potential as a diagnostic and prognostic methodology that can be used to stratify patients and provide customised therapy. Immunomodulatory therapies, especially intravenous immunoglobulin (IVIG), are potentially effective in a limited range of patient populations, but clinical response is variable. On the whole, this review demonstrates the role of immunoglobulin-mediated mechanisms in RPL and their future potential in enhancing precision medicine approaches to better diagnosis and management.

Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Synthesis strategies, nutrient delivery mechanisms, and pathways toward sustainable agriculture via nano-fertilizers - Praveen Mallari; Venkatachalam Deepa Parvathi; V. Sathishkumar; R. B. Jeen Robert; M. Joemax Agu; M. Muthuselvi; G. S. Hikku (Journal of Crop Science and Biotechnology, 2026)

Sickle cell disease-related myths and misconceptions among tribal communities in India: a multi-state qualitative study - Yogita Sharma; Parikipandla Sridevi; Jatin Sarmah; Godi Sudhakar; Manoranjan Ranjit; Shaily B. Surti; Deepa Bhat; Madhusmita Bal; Rabindra K. Jena; Bontha V. Babu (Journal of Community Genetics, 2026)

Sociodemographic characteristics and healthcare-seeking behaviour of patients with sickle cell disease: a cross-sectional study across five tribal districts in India - Parikipandla Sridevi; Inti Anil; Jatin Sarmah; Madhusmita Bal; Shaily B. Surti; Deepa Bhat; Manoranjan Ranjit; Yogita Sharma; Bontha V. Babu (Journal of Community Genetics, 2026)

Emerging technologies in watermelon juice Processing: Innovations in preservation and quality enhancement - G. Jeevarathinam; Vismaya K. Sachithanandhan; J. Deepa; V. Arun Prasath; S. Ganga Kishore; Punit Singh; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Control, 2026)

Deacidification of vegetable oils: advanced technologies, mechanistic insights, and emerging strategies - G. Jeevarathinam; R. Rahul; J. Deepa; N. Sharath Kumar; C.S. Neethu; G. Sarojini; V. Siva Shankar; Punit Singh; Davinder Pal Singh Oberoi; Sarvesh Rustagi; Syed Mohammed Basheeruddin Asdaq (Food Chemistry, 2026)

Spectroscopic Analysis of 4-MeO-TPA with Metal Oxide Nano-Assembly: Insights on Fluorescence Quenching and FRET - V. V. Koppal; R. Venkatesh; N. R. Banapurmath; Kalpana Sharma; Deepa H. K (Journal of Fluorescence, 2025)

The influence of climate modes on long-term sea level variability of the Indian ocean with special emphasis on the Southern Annular Mode: A study based on Indian ocean sea level reconstructions - J. S. Deepa; C. Gnanaseelan; K. V. Anusree (Theoretical and Applied Climatology, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Genetic Variability in Jackfruit (Artocarpus heterophyllus Lam.) for Floral Traits and Fruit Quality Attributes in Eastern Tropical Region of India - Kundan Kishore; Deepa Samant; V. Pandey (Applied Fruit Science, 2025)

Spectroscopic and Computational Analysis of 5PPD-CeO2: Insights from Fluorescence Quenching and FRET Studies - Kalpana Sharma; Varsha V. Koppal; Raviraj Kusanur; Deepa H. K (Journal of Fluorescence, 2025)

Assessment of the Soil Erosion Susceptibility Zones in Tea Plantation Areas of Jalpaiguri District, India: An Integrated Approach of RUSLE and WLC Model - Manika Mallick; Y. V. Krishnaiah; Kausik Panja; Deepa Rai; Debasis Das; Moumita Hati; Atoshi Chakma (Journal of the Indian Society of Remote Sensing, 2025)

Experimental investigation of shrouded tomato storage systems in mitigating losses during long-distance transportation - G. Hari Pranesh; S. Ganga Kishore; P.L. Meenakshi; V. Arun Prasath; Madhuresh Dwivedi; J. Deepa; R. Pandiselvam; M. Arulkumar (Journal of Stored Products Research, 2025)

Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

Evaluation of diverse blackgram (Vigna mungo (L.) Hepper) germplasm accessions for root-knot nematode resistance and genetic diversity study - Bharat H. Gawade; Lovely Kumari; Zakaullah Khan; Ankit Saroha; Shraddha Ujjainwal; Deepa Pal; Gayacharan; Kuldeep Tripathi; Padmavati G. Gore; V. Celia Chalam; Dhammaprakash Pandhari Wankhede (Genetic Resources and Crop Evolution, 2025)

Land suitability assessment for tea cultivation in Jalpaiguri district of West Bengal, India, using AHP and DEMATEL techniques - Manika Mallick; Y. V. Krishnaiah; Kausik Panja; Debasis Das; Deepa Rai; Moumita Hati; Atoshi Chakma (Environment, Development and Sustainability, 2024)

Fertile grounds: exploring male sterility in cotton and its marker development - V. Deepa Dharsini; A. Subramanian; N. Premalatha; N. Manikanda Boopathi; M. Djanaguiraman; V. P. Santhanakrishnan (Molecular Biology Reports, 2024)

Cinnamon essential oil incorporated chitosan submicron emulsion as a sustainable alternative for extension of mango shelf life - Vinayak V. Deshi; Mallikarjun G. Awati; Deepa Terdal; S.N. Patil; Anita R. Ghandhe; Avinash S. Gudigennavar; Pooja Patalli; Deep Lata; Duniya Ram Singh; Mohammed Wasim Siddiqui (Sustainable Chemistry and Pharmacy, 2024)

Exploring the molecular binding mechanism of 6-fluoro, 4-hydroxy, 2- methyl quinoline with TiO2 nanoparticles: A spectroscopic, thermodynamic, and insights into the solvatochromic effect - Deepa H. Krishne; Kalpana Sharma; A. Jagannatha Reddy; V. V. Koppal (Journal of Fluorescence, 2024)

Recent progress and major gaps in the vaccine development for African swine fever - M. S Chandana; Sonu S. Nair; V. K. Chaturvedi; Abhishek; Santanu Pal; Manchikanthi Sri Sai Charan; Shilpa Balaji; Shubham Saini; Koppu Vasavi; Poloju Deepa (Brazilian Journal of Microbiology, 2024)

Performance evaluation of dimensionality reduction techniques on hyperspectral data for mineral exploration - Deepa C; Amba Shetty; Narasimhadhan A V (Earth Science Informatics, 2023)

Sickle cell disease-related knowledge and perceptions of traditional healers in tribal communities in India: implications on sickle cell disease programme - Bontha V. Babu; Parikipandla Sridevi; Shaily B. Surti; Deepa Bhat; Jatin Sarmah; Godi Sudhakar; Yogita Sharma (Journal of Community Genetics, 2022)

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

Automated grading of diabetic retinopathy using CNN with hierarchical clustering of image patches by siamese network - V. Deepa; C. Sathish Kumar; Thomas Cherian (Physical and Engineering Sciences in Medicine, 2022)

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

Peripheral health workers’ knowledge and experience related to sickle cell disease: an in-depth interview study in six tribal-dominated districts of India - Bontha V. Babu; Parikipandla Sridevi; Shaily B. Surti; Manoranjan Ranjit; Deepa Bhat; Jatin Sarmah; Godi Sudhakar; Yogita Sharma (Journal of Community Genetics, 2022)

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

High-frequency direct shoot induction from leaf explants of Pogostemon quadrifolius (Benth.) F. Muell.: an ethnomedicinal herb - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2022)

Correction to: A cost-effective and efficient approach for generating and assembling reagents for conducting real-time PCR - Ridim D Mote; Shinde Laxmikant V; Surya Bansi Singh; Mahak Tiwari; Hemant Singh; Juhi Srivastava; Vidisha Tripathi; Vasudevan Seshadri; Amitabha Majumdar; Deepa Subramanyam (Journal of Biosciences, 2022)

A cost-effective and efficient approach for generating and assembling reagents for conducting real-time PCR - Ridim D Mote; V Shinde Laxmikant; Surya Bansi Singh; Mahak Tiwari; Hemant Singh; Juhi Srivastava; Vidisha Tripathi; Vasudevan Seshadri; Amitabha Majumdar; Deepa Subramanyam (Journal of Biosciences, 2021)

Atmospheric Aerosol Scattering Coefficients in a Broad Visible Spectral Region - R. Arun; P. Anoop; S. John; J. Chen; V. Deepa; R. Varma (Aerosol Science and Engineering, 2021)

Synthesis and Characterization of a Novel Heterocyclic Schiff Base and Development of a Fluorescent Sensor for Vitamin B12 - Savitha Devaswamparambil Pradeep; Deepa Sebastian; Anjali Krishna Gopalakrishnan; Divya Kizhakkeppurath Manoharan; Dhanya Thaikatt Madhusudhanan; Puzhavoorparambil V. Mohanan (Journal of Fluorescence, 2021)

In vitro strategies for the conservation of Indian medicinal climbers - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2020)

Evaluation of oxidative stress in caprine anaplasmosis and effect of vitamin E–selenium in monitoring oxidative stress - G. Dhanasree; Usha Narayana Pillai; Chirayath Deepa; V. R. Ambily; M. Shynu; C. Sunanda (Tropical Animal Health and Production, 2020)

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

A new mouse model of frailty: the Cu/Zn superoxide dismutase knockout mouse - Sathyaseelan S. Deepa; Shylesh Bhaskaran; Sara Espinoza; Susan V. Brooks; Anne McArdle; Malcolm J. Jackson; Holly Van Remmen; Arlan Richardson (GeroScience, 2017)

Influence of Drying Temperature on Three Soils Physical Properties - B. M. Sunil; A. V. Deepa (Geotechnical and Geological Engineering, 2016)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

Acute Toxicity Assessment of Reactive Red 120 to Certain Aquatic Organisms - R. Darsana; G. Chandrasehar; V. Deepa; Y. Gowthami; T. Chitrikha; S. Ayyappan; A. Goparaju (Bulletin of Environmental Contamination and Toxicology, 2015)

Fructose induces mitochondrial dysfunction and triggers apoptosis in skeletal muscle cells by provoking oxidative stress - Natasha Jaiswal; Chandan K. Maurya; Deepti Arha; Deepa R. Avisetti; Ayyappan Prathapan; Palayyan S. Raj; Kozhiparambil G. Raghu; Shasi V. Kalivendi; Akhilesh Kumar Tamrakar (Apoptosis, 2015)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

A simple and efficient protocol for isolation of high quality functional RNA from different tissues of turmeric (Curcuma longa L.) - K. Deepa; T. E. Sheeja; R. Santhi; B. Sasikumar; Anu Cyriac; P. V. Deepesh; D. Prasath (Physiology and Molecular Biology of Plants, 2014)

Accumulation of mercury and other heavy metals in edible fishes of Cochin backwaters, Southwest India - Mahesh Mohan; M. Deepa; E. V. Ramasamy; A. P. Thomas (Environmental Monitoring and Assessment, 2012)

Effectiveness of Treatment Technologies for Wastewater Pollution Generated by Indian Pulp Mills - Deepa K. Tiku; Anil Kumar; S. Sawhney; V. P. Singh; Rita Kumar (Environmental Monitoring and Assessment, 2007)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

STUDIES ON NOVEL NON-IMIDAZOLE HUMAN H4 RECEPTOR ANTAGONISTS USING GFA AND FREE-WILSON ANALYSIS - Surekha R. Pimple; Mandar A. Kelkar; Deepa V. Pednekar; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

3D QSAR STUDIES OF INHIBITORS OF EPIDERMAL GROWTH FACTOR RECEPTOR [EGFR] USING CoMFA AND GFA METHODOLOGIES - Deepa V. Pednekar; Mandar A. Kelkar; Surekha R. Pimple; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

3D QSAR STUDIES OF INHIBITORS OF CHOLESTEROL ESTER TRANSFER PROTEIN (CETP) BY CoMFA, CoMSIA AND GFA METHODOLOGIES - Mandar A. Kelkar; Deepa V. Pednekar; Surekha R. Pimple; Krishnacharya G. Akamanchi (Medicinal Chemistry Research, 2004)

Trace Metal Concentration in Scalp Hair of Occupationally Exposed Autodrivers - H. Vishwanathan; A. Hema; Deepa Edwin; M. V. Usha Rani (Environmental Monitoring and Assessment, 2002)